2020
DOI: 10.3892/ijo.2020.5050
|View full text |Cite|
|
Sign up to set email alerts
|

circRNA_001275 upregulates Wnt7a expression by competitively sponging miR‑370‑3p to promote cisplatin resistance in esophageal cancer

Abstract: Circular RNAs (circRNAs) are aberrantly expressed in various tumors and are associated with tumorigenesis. The present study aimed to determine the role of circRNA_001275 in cisplatin-resistant esophageal cancer. Three pairs of cisplatin-resistant tissues and corresponding adjacent tissues were collected and subjected to circRNA chip analysis. Additionally, the effect of circRNA_001275 on cisplatin-resistant cells was investigated. The relationship between circRNA_001275, microRNAs (miRs) and target genes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…The RNA sample was reverse transcribed by the Reverse Transcriptase Kit (Takara, Beijing, China). Real-time PCR was performed with the CFX Connect Real-time PCR Machine (Bio-Rad) and SYBR green reagent, as described previously ( Zou et al, 2020 ). GAPDH was used as internal controls.…”
Section: Methodsmentioning
confidence: 99%
“…The RNA sample was reverse transcribed by the Reverse Transcriptase Kit (Takara, Beijing, China). Real-time PCR was performed with the CFX Connect Real-time PCR Machine (Bio-Rad) and SYBR green reagent, as described previously ( Zou et al, 2020 ). GAPDH was used as internal controls.…”
Section: Methodsmentioning
confidence: 99%
“…StepOnePlus system (Applied Biosystem, USA) was utilized to carry out real-time PCR by the use of Thermo Fisher Scientific Maxima SYBR Green/ROX qPCR Master Mix assay (2×) (#K0221). In addition, the BioRad CFX Connect Real-time PCR machine (Biorad) and Universal SYBR green reagent were adopted for real-time PCR based on the previous study (14). GAPDH and U6 were used as endogenous reference.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…Total RNA was also reverse-transcribed by a MicroRNA Reverse Transcription Kit (Applied Biosystems, Foster City, CA, USA). The qRT-PCR assays were performed as previously reported ( 12 ). GAPDH and U6 were used as internal controls for circRNAs and miRNAs, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that circLPAR3 could target miR-198 to promote ESCC metastasis ( 11 ). CircRNA_001275 is a sponge of miR-370-3p to enhance cisplatin resistance in ESCC ( 12 ). CircPVT1 could target miR-4663 to promote EC proliferation ( 6 ).…”
Section: Introductionmentioning
confidence: 99%